Thermophilic Hadarchaeota grow on long-chain alkanes in syntrophy with methanogens - Tiantian Yu; Lin Fu; Yinzhao Wang; Yijing Dong; Yifan Chen; Gunter Wegener; Lei Cheng; Fengping Wang (Nature Communications)
Abstract Methanogenic hydrocarbon degradation can be carried out by archaea that couple alkane oxidation directly to methanogenesis, or by syntrophic associations of bacteria with methanogenic archaea. However, metagenomic analyses of methanogenic environments have revealed other archaea with potential for alkane degradation but apparent inability to form methane, suggesting the existence of other modes of syntrophic hydrocarbon degradation. Here, we provide experimental evidence supporting the existence of a third mode of methanogenic degradation of hydrocarbons, mediated by syntrophic cooperation between archaeal partners. We collected sediment samples from a hot spring sediment in Tengchong, China, and enriched Hadarchaeota under methanogenic conditions at 60 °C, using hexadecane as substrate. We named the enriched archaeon Candidatus Melinoarchaeum fermentans DL9YTT1. We used 13C-substrate incubations, metagenomic, metatranscriptomic and metabolomic analyses to show that Ca. Melinoarchaeum uses alkyl-coenzyme M reductases (ACRs) to activate hexadecane via alkyl-CoM formation. Ca. Melinoarchaeum likely degrades alkanes to carbon dioxide, hydrogen and acetate, which can be used as substrates by hydrogenotrophic and acetoclastic methanogens such as Methanothermobacter and Methanothrix.